COMPARISON OF RAINFALL ESTIMATION VALUE CAUSED FLOOD USING CST AND MCST METHODS - Rayhan Rinanto; Aditya Mulya (Geography Education Study Program, Faculty of Teacher Training and Education, 2022)
Hydrometeorological disasters such as general flooding have occurred in the BMI (Indonesian Maritime Continent) area. One of the cases occurred in 2 sub-districts in Kudus Regency on February 1, 2021. However, limited tools were an obstacle to measuring the falling rainfall and it was very difficult to detect the clouds that caused the rain. Therefore, the rainfall estimation method using the CST and mCST methods is used to find out the results of the rainfall estimation and how to compare the two methods. The data used is Himawari-8 Satellite data along with supporting data from the BMKG Rain Post around the research location. The data is then processed using Google Collaboratory and analyzed quantitatively. The results of this study indicate that the correlation of the value of the estimated rainfall using the CST and mCST methods to the rainfall value of the observation data in the three research areas has a very low value. In addition, the precipitation that occurs tends to be caused by stratiform clouds (Dense Cirrus).